Perceptions and utilization of tele-orthodontics: a survey of the members of the American Association of Orthodontists - Sarah Abu Arqub; Dalya Al-Moghrabi; Chia-Ling Kuo; Lucas Da Cunha Godoy; Flavio Uribe (SpringerOpen, 2024)
Abstract Objective This study aimed to investigate orthodontists' utilization and perceptions of tele-orthodontics. Materials and methods A 30-item online survey was distributed to members of the American Association of Orthodontists (AAO). The questionnaire encompassed topics concerning the orthodontists' utilization, perceptions, clinical applications, limitations, and concerns regarding tele-orthodontics. Descriptive statistics were employed, and comparisons between responses from users and non-users were conducted  using Wilcoxon rank-sum tests and Fisher's exact tests. Results 152 members completed the survey, (response rate: 2.4%). More than two third of respondents (69.74%) were users of tele-orthodontics. Users were more aligned with the belief that tele-orthodontics facilitates effective communication (mean ± standard deviation (SD) 4.06 ± 0.83 vs. 3.33 ± 0.94, p < 0.001). Both groups agreed on the requirement of patient fees for tele-orthodontic visits (mean ± SD: 3.62 ± 1.11 users vs. 3.74 ± 1.02 non-users, p = 0.659), and on the capability  of the system to reduce unwarranted referrals (p = 0.20). The majority of participants acknowledged  the utility of the system in monitoring aligners' patients (89% in users vs. 61% in non-users, p < 0.001). Non-users expressed greater concerns regarding privacy risks (mean ± SD: 3.06 ± 0.97 users vs. 3.57 ± 0.86 non-users, p = 0.002). Both groups stressed the significance of obtaining informed consent before utilizing tele-orthodontics. Conclusions The widespread acceptance of tele-orthodontics among AAO members was apparent, as demonstrated by their recognition of its effectiveness. There was notable variation in how users and non-users perceived tele-orthodontics. The study's results offer valuable insights into both the potential benefits and drawbacks of incorporating this technology into clinical practice from the clincians' perspective.